A Biostimulant from Kappaphycus alvarezii Enhances the Growth and Development of Basil (Ocimum basilicum L.) Plants - Aline Nunes; Felipe de Souza Dutra; Lohan Rodrigues Brandão Santos; Camila Pimentel Martins; Alex Ricardo Schneider; Eva Regina Oliveira; Milene Stefani Pereira-Vasques; Gadiel Zilto Azevedo; Jorge Luiz Barcelos Oliveira; Valéria Cress Gelli; Alex Alves dos Santos; Marcelo Maraschin; et al. (Horticulturae)
This study evaluated the efficacy and optimal concentrations of Kappaphycus alvarezii biostimulant from São Paulo (Kal-SP) and Santa Catarina (Kal-SC) for the hydroponic cultivation of basil (Ocimum basilicum). Basil plants were grown with 1%, 3%, 5%, and 7% concentrations of each extract using distilled water as a control. The extracts were applied via weekly foliar sprays. Morphological and biochemical parameters, in addition to the biogenic amine profile, were evaluated. Morphologically, 3% Kal-SP increased plant height by 17.1% and length of the roots by 54.8%, while 3% and 5% Kal-SC enhanced node number by 95.2% and 120.2%, respectively. Biochemically, 5% Kal-SP and 1% and 7% Kal-SC maximized chlorophyll and carotenoid content, 5% Kal-SP and 5–7% Kal-SC increased soluble sugars, and 7% Kal-SP and 3–7% Kal-SC elevated starch. Amino acid levels were the highest with 7% Kal-SP and 5% Kal-SC. The biogenic amine profile was also modulated by the K. alvarezii extracts, demonstrating their ability to influence compounds of interest. The results suggest that 3% or higher concentrations of these extracts can be beneficially applied to basil cultivation, with potential variations depending on the seaweed’s geographic origin.